MONEY POLITICS PEMILU 2019 (Analisis Framing Di Sindonews, Kompasnews.com, dan Cnn Indonesia) - SABRON HAKIM (TASÂMUH, 2019)
This research discusses the media that frame and constructs news about political money in the 2019 elections on sindonews, kompasnews.com, and CNN Indonesia. The raming analysis used in this study is Robert N. Entman's framing which discusses the problem that determines, what / who causes the problem, what moral decisions are in the news and what is offered by the publisher. The results of this study show the facts in constructing and framing political money cases in Sindonews, Kompasnews and CNN Indonesia. Sindonews members report political problems that occur, without raising one group and demeaning another group. This media wants to prove the fact that money politics does occur in the community, spearheaded by sympathetic officials, as well as people concerned. While the online media CNN Indonesia was welcomed more favourably (pro) to the Jokowi-Ma'ruf pair, because it had been clearly informed and reported several times about the practices of money politics related to Gerindra political parties, and also related to the party PKS because all of the political parties are Prabowo-Sandi candidate pairs.